South East Europe Regular Economic Report, No. 8S, Fall 2015 : The Impact of Aging on Economic Growth - World Bank Group (World Bank, Washington, DC, 2016)
The six countries of South East Europe (SEE6) are aging fast and catching up with developed economies that are already far advanced in the aging process. Low fertility rates are reducing working-age populations across the SEE6. The adverse SEE6 demographic dynamic is aggravated by emigration. In the absence of any policy and behavioral responses or changes in labor productivity, and where population aging reflects solely declining overall labor force participation rates, aging itself would be expected to negatively impact economic growth. Boosts in productivity are one of the key ways to counterbalance potential negative effects of aging on economic growth. Changes in both individual and business behavior supported by policies that increase quality of human capital and encourage labor force participation can help seize the opportunities and mitigate the adverse effects of an aging population.